1H-NMR fingerprinting of brown rice syrup as a common adulterant in honey. Issue 34 (15th August 2016) - Musharraf, Syed Ghulam; Ambreen Fatima, Syeda; Siddiqui, Amna Jabbar; Iqbal Choudhary, M.; Atta-ur-Rahman
Abstract : Honey is often adulterated because of its high economic value and increasing consumption. Abstract : Honey is often adulterated because of its high economic value and increasing consumption. Among the most common adulterants, brown rice syrup (B.R.S.) is relatively difficult to detect. We present here a simple and fast quantitative 1 H-NMR method to identify adulteration of honey by brown rice syrup using the concentration conversion factor. The principal component analysis of the 1 H-NMR spectra of honey and B.R.S. showed a characteristic pattern at δ H 5.39 for B.R.S. identification. Good linearity ( r 2 = 0.9713) was obtained between the % B.R.S. in honey and the integrated area of the peak at δ H 5.39. With the newly developed method, we successfully quantified B.R.S. in two commercial honey samples at 22.3% and 37.3% with a precision of 0.1–1%. As a result, a simple, efficient and precise 1 H-NMR method was developed to quantitatively identify the presence of B.R.S. in honey without any complicated sample preparation.